Pengaruh Store Atmosphere Dan Kualitas Produk Terhadap Kepuasan Konsumen Persebaya Store Di Surabaya - Permana, Dodi; Satriyono, Gandung (Politeknik Raflesia Press, 2024)
The purpose of this study is to identify: (1) Toko quality and its impact on customers' satisfaction at Persebaya Store; (2) Product quality and its impact on customers' satisfaction; and (3) The relationship between product quality and store quality and customer satisfaction. Utilising a sample of 100 respondents who are Persebaya Store customers in Surabaya, the analysis technique is a berganda line regression. According to the study's findings, there are three variables that influence consumer behaviour: (1) toko size contributes positively and significantly to the change in behaviour; (2) product quality also contributes positively and significantly to the change in behaviour; and (3) both toko size and product quality contribute positively and significantly to the change in behaviour.